Rectangular small patch antenna - Kubura, Sejma; Imeci, Sehabeddin Taha; Uslu, Ahmet Fehim (Sustainable Engineering and Innovation, 2024)
This paper discusses various challenges related to the antenna design process for sub 6 GHz, 5G communications. In the first example, the design is a square, simple antenna with two slots. Their parametric studies are made to see which parameters have affected the results. On the other hand, the second design for the antenna is represented as well, the design is still like a square, but the number of slots is bigger. The circular design of the antenna is also one of the most popular for 5G, but the results are not so good. For this kind of antenna below 6 GHz, a few slots are important, and a circular design is not the best idea. This antenna, the second design operates at 3.23 GHz with S11 of -14.3 dB, E-Theta of 5.73 dB, and E-Phi of -11.6 dB.